Experimental study on the indenting, buckling and piercing of aluminum beverage cans - Neo, Wee Boon. (2009)
The aluminum beverage can is a familiar sight all around the world, notably especially in more developed nations. As countries become more affluent, beverage consumption goes up, as such the containers used to hold them. As a study has shown in 2006, 224 billion packaged beverages were sold in the US, of which 102 billion were aluminum cans. In the same year, Europe consumed more than 45 billion cans. The familiar pop that every can makes as we open them is already such a common happening that we do not realize the scale of the aluminum that we actually consume. In view of this figures, this project seeks to understand the aluminum can in more detail. With more understanding of the structural and mechanics of the aluminum can, the aluminum beverage can may be redesigned and manufactured with lesser materials in mind. Imagine a 1 gram savings in each aluminum can will result in savings of 102 billion grams of aluminum! This project will focus more on understanding the aluminum beverage can initially, with the aim of allowing future projects to explore more into the design and mechanics of the can with ultimate goal of designing and manufacturing a lighter and more environmental beverage can. Firstly, a study into the manufacturing process of the aluminum beverage can is done. This will enable an initial understanding of the structure of the can. Also, the type of can to be used for the purpose of the project will be chosen and set. Next, the parameters of the projects will be set and test procedures to be devised. Since the project seeks to understand the indentation and buckling of the aluminum beverage can, the can will be tested via axial loading under various degree of indentation. Preparation of samples will be done on a standard procedure to ensure homogeneity of results and same goes for the test procedure. As a project of this sort is the first in NTU, all these will be done using whatever resources available locally, whereas suggestions on how to enhance the accuracy of the results and further research will be recommended. Lastly, the results of the tests conducted will be documented in this report. An initial understanding and findings of the aluminum beverage can will be presented thereafter.